Effectiveness of Reminiscence Therapy on Elderly Depression - Pratama, Aditha Angga; Putu Agus Ariana (HealthCare Nursing Journal, 2025)
Depression is a common mental health issue among older adults, especially in rural areas where access to psychosocial support is limited. One promising non-pharmacological approach is reminiscence therapy (RT), which encourages emotional expression and social connection through structured memory-sharing. This study aimed to evaluate the effectiveness of community-based reminiscence therapy in reducing depressive symptoms among elderly individuals at the Kubutambahan I Public Health Center in Bali, Indonesia. A quasi-experimental pre-test–post-test control group design was used with 40 elderly participants divided evenly into intervention and control groups. Depression levels were assessed using the Geriatric Depression Scale (GDS-15). Demographic data were comparable between groups. Post-intervention results showed a significant decrease in mean GDS scores in the intervention group (from 9.1 to 5.4; p < 0.001), while the control group experienced no significant changes. Qualitative feedback highlighted improvements in emotional relief and social engagement. Reminiscence therapy significantly reduced depression in elderly participants in a short period. This intervention should be integrated into primary care services, particularly in rural settings, to enhance elderly mental health through scalable, community-based approaches.